Armenian teachers' dichotomous perspectives on children with high‐functioning autism. Issue 2 (31st July 2019) - Allan, David; Hallett, Fiona; Hallett, Graham
Abstract: This article uses the views of student teachers and serving teachers from a post‐Soviet context in order to better understand current thinking around teachers' perceptions of children with what might be termed 'hidden' disabilities. Drawing on social comparison theory, and adopting a phenomenographical approach, the study explores teachers' perspectives of autism in the Republic of Armenia, offering an insight into the impact of its social, cultural and political history. Whilst serving teachers demonstrated contrastive and downward comparisons when presented with a vignette of a young person with Asperger's Syndrome, student teachers expressed more connective comparisons. The data suggest, then, that Armenian student teachers represent progressive attitudinal change towards individuals with disabilities. These results also shed light on how social comparison theory might be used to tease out assumptions and taken‐for‐granted attitudes in the global West.